British Thoracic Society guidelines for the management of community acquired pneumonia in children: update 2011. (8th September 2011) - Harris, Michael; Clark, Julia; Coote, Nicky; Fletcher, Penny; Harnden, Anthony; McKean, Michael; Thomson, Anne
Abstract : The British Thoracic Society first published management guidelines for community acquired pneumonia in children in 2002 and covered available evidence to early 2000. These updated guidelines represent a review of new evidence since then and consensus clinical opinion where evidence was not found. This document incorporates material from the 2002 guidelines and supersedes the previous guideline document.